Gambaran Tingkat Kecemasan dan Stres Kerja Tenaga Kesehatan Puskesmas Saat Pandemi Covid-19 - Hendryk Priyatna; Muhammad Mu’in; Elsa Naviati; Sari Sudarmiati (Holistic Nursing and Health Science, 2021)
Introduction: The rapid growth of number of COVID-19 cases every day has made the condition of health workers increasingly depressed. These conditions can affect the level of anxiety and work stress. A study involving health workers caring for Covid-19 patient showed anxiety symptoms and work stress experience. The existence of anxiety and work stress can have an impact on increasing work errors, deteriorating physical and mental conditions, reducing productivity and  decreasing service’s quality. This study aims to describe the anxiety level and work stress of health workers during Covid-19 pandemic at the Public Health Center (Puskesmas). Methods: This research was a descriptive survey study with 156 respondents from nine Puskesmas obtained through cluster and quota sampling calculation. Data was taken using Depression Anxiety Stress Scale (DASS-42) and workplace Stress Scale (WSS) questionnaires which distributed via google form. Results: The results of this study obtained 16.7% of Puskesmas health workers experience anxiety consisting of 5.8% mild, 7.7% moderate, 2.6% severe and 0.6% very severe anxiety. Meanwhile, the work stress study obtained as many as 68.7% experience work stress, consisting of low 35.3%, moderate 27.6%, and heavy work stress 5.8%. Conclusion: Failure to manage anxiety and work stress can have a negative impact on mental health and can even endanger the lives of health workers. The findings in this study indicate risk for mental health disorders for health workers due to the Covid-19 pandemic. So it is necessary for relevant agencies and also individual itself, to manage anxiety and work stress.